The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1007/s003300000586
|View full text |Cite
|
Sign up to set email alerts
|

Direct contrast-enhanced 3D MR venography

Abstract: Non-enhanced two-dimensional (2D) time-of-flight (TOF) MRA is well established for imaging of the deep venous system. However, based on the acquisition of multiple axial images, it can be time-consuming and often fails to delineate small superficial and perforating veins. The presented low-dose, direct-contrast-injection 3D MR venography technique allows rapid acquisition of high-quality MR venograms and can be employed for the display of the deep and superficial venous system of upper and lower extremity incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 26 publications
(28 reference statements)
0
39
0
3
Order By: Relevance
“…The analysis in this study could be used to determine the appropriate dilution of these agents to ensure the optimal contrast agent concentration is not exceeded. Ruehm et al reported using a 1:15 dilution of gadopentatate dimeglumine, i.e., 33 mM, with TR/TE/flip ¼ 5.2 ms/ 1.5 ms/30 (30). Based on published values of relaxivity for gadopentatate dimeglumine (14) and TR/TE ¼ 5.2 ms/ 1.5 ms, we predict an optimal concentration of 52 mM (i.e., 1:10 dilution).…”
Section: Figmentioning
confidence: 94%
“…The analysis in this study could be used to determine the appropriate dilution of these agents to ensure the optimal contrast agent concentration is not exceeded. Ruehm et al reported using a 1:15 dilution of gadopentatate dimeglumine, i.e., 33 mM, with TR/TE/flip ¼ 5.2 ms/ 1.5 ms/30 (30). Based on published values of relaxivity for gadopentatate dimeglumine (14) and TR/TE ¼ 5.2 ms/ 1.5 ms, we predict an optimal concentration of 52 mM (i.e., 1:10 dilution).…”
Section: Figmentioning
confidence: 94%
“…Among them, MRI is a minimally invasive and reproducible modality, which has been applied using a variety of techniques. While most MRI techniques depict vessels as hyperintense structures and capture thrombi as signal voids [6][7][8][9][10][11], other techniques are aimed at directly visualising venous thrombi [12][13][14] and, in combination with each other, are expected to improve imaging characterisation.…”
Section: Discussionmentioning
confidence: 99%
“…Reported CE-MR venography techniques use either direct injection of diluted contrast-media (1:15 to 1:25 ml of gadolinium chelate in saline solution) in the ipsilateral extremity or contralateral intravenous injection of non- diluted contrast-media, and acquisition during delayed venous enhancement after initial arterial first pass [59,60]. Both techniques have their strengths and weaknesses.…”
Section: Venous Assessmentmentioning
confidence: 99%
“…Direct CE-MR venography is easy to perform, well tolerated and highly accurate for detection of venous stenosis and obstructions in the upper extremity and central veins [59,60,[63][64][65]. Furthermore, direct CE-MR venography diameter measurements are more accurate compared with duplex ultrasonography when using surgical measurements as standard of reference [54].…”
Section: Venous Assessmentmentioning
confidence: 99%